Membangun Budaya Birokrasi Dalam Menghadapi Revolusi Industri 4.0 - Firman Hadi Rivai (Jurnal Transformasi Administrasi, 2019)
The industrial revolution 4.0 has changed lifestyle the community instantly. This also occured in the public service sector. In addition, the community expecting the practical,responsive, and aspirational public service. To answer the challenge, bureucracy should be capable for adapting to the situation, in order not to lose community trust. On this adaptation process, one of the alternatives that should be done is to build and develop culture bureaucratic compatible with the raise of industrial revolution 4.0. Culture that is built in and developed should be internalised into attitudes and behaviour of apparatus bureaucracy in the daily performance on duties. of public service.